Applications of numerical modelling for strata control in mines - Singh G.S.P.; Singh U.K.; Murthy V.M.S.R. (My University, 2025)
A proper understanding of complex behaviour of rock mass has always been difficult for reliable design and safe operation of mining structures. Numerical modelling has emerged as a popular tool solving the static as well as the dynamic processes assisting in proper design and operation of the structures. This paper introduces the basics of different numerical modelling approaches and underlines their strength and limitations. Various applications of numerical modelling techniques for strata management in mines are discussed. Practical examples of a few of the issues like pillar design, soft floor behaviour, shotcrete support design, and prediction of caving behaviour and support selection for longwall workings etc., as studied by the authors, are also illustrated. © 2010 Springer Science+Business Media B.V.